Acid saline fluid inclusions: examples from modern and Permian extreme lake systems. Issue 4 (15th July 2013) - Benison, K. C.
Abstract: Some of the Earth's most extreme aqueous chemistries are found at acid saline lakes and associated shallow groundwaters. Modern lakes and groundwaters in Western Australia have pHs as low as 1.5, total dissolved solids as high as 32%, unusually high concentrations of Al, Si, Fe, As, and Sb, and many other chemical characteristics atypical of natural waters. Analogous Permian red bed and evaporite lake deposits in the US midcontinent also had extreme water compositions, including negative pH. Fluid inclusions in chemical sediments from modern and Permian acid saline lakes record specific physical, chemical, and biological conditions. Primary inclusions in this bedded halite and gypsum are trapped shallow lake water, air bubbles, crystals of other minerals, and microorganisms and organic compounds. Isolated fluid inclusions in early diagenetic phases of halite are remnants of shallow groundwaters and can be analyzed to determine chemical compositions of past groundwaters. A variety of traditional methods, including petrography, freezing–melting microthermometry and laser Raman spectroscopy, and innovative variations, such as homogenization of artificially nucleated vapor bubbles and UV‐vis petrography, produce data detailing environmental conditions. Other traditionally used methods, such as laser ablation ICP‐MS, are not effective due to the inclusions' high and complex salinity, extremely low pH and/or low pressure. Making synthetic solutions that match the complexity of natural acid saline inclusions is another challenge. Fluid inclusions in acid‐precipitated halite have proven to be excellent repositories for past surface chemical, physical, and biological conditions. Although the methods used and data obtained from acid‐precipitated halite and gypsum are not exactly the same as for neutral‐alkaline evaporites, acid inclusions provide high‐resolution environmental data for modern and ancient extreme environments. These extreme fluids may also have similarities to other past extreme environments, to ore mineralizing fluids, and to past liquids on Mars. Abstract : Primary fluid inclusions in halite and gypsum from modern and Permian acid saline lakes record specific physical, chemical, and biological conditions, including low pH and acidophilic and halophilic microorganisms. A variety of traditional methods, including petrography, freezing/melting microthermometry and laser Raman spectroscopy, and innovative variations, such as homogenization of artificially‐nucleated vapor bubbles and UV‐vis petrography, produce data detailing extreme environmental conditions in the rock record.